Analisis Hubungan Digital Marketing Skills Dengan Kinerja Penjualan Produk Mahasiswa di Marketplace Shopee - Paula Florensia Munthe; Rina Kartika Warasati; Azra Lena Nuraina; Naila Zuhra; Muhammad Ilham Fiqri (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the relationship between Digital Marketing Skills and the Sales Performance of Student Products on the Shopee Marketplace. The research employed a quantitative associative method, with a sample of 52 students actively selling on Shopee, selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using normality, linearity, and Pearson correlation tests with SPSS 26. The results prove a strong and significant positive relationship between the two variables, with a Pearson correlation coefficient of 0.795 and a significance of 0.000. This indicates that the higher the students' digital marketing skills such as online promotion, account management, and content creation the higher the sales performance of their products on the Shopee Marketplace. These findings reinforce the Resource-Based View (RBV) theory, which positions digital skills as a strategic internal resource for achieving a competitive advantage and enhancing sales performance in the digital economy era